Análisis del riesgo en el ciclo de ventas en la Empresa Representaciones SAS (2024)
This paper investigates the risk in the sales cycle in a trading company. Its purpose is to identify and evaluate the risks in the sales area in order to improve organizational risk management. The different sub-processes of the sales cycle were analyzed through interviews, observations and documentary analysis. The results show tolerable risks, keeping under control those processes considered highly vulnerable to fraud. In addition, effective risk management practices were identified, which will enable managers to monitor their impact on their activities.